Their finest [videorecording (DVD)] - Arterton, Gemma; Claflin, Sam, 1986-; Nighy, Bill, 1949- (EuropaCorp, 2017)
In 1940 set in London the story is an ode to how women played a major role in boosting national morale during the Blitz of London in the second world war.